A New Approach to the Economics of Health Care - Olson, Mancur; American Enterprise Institute for Public Policy Research (Washington, D.C.: American Enterprise Institute for Public Policy Research, 1981)
This volume is one of a series of studies and conference proceedings on health care financing and regulation published by AEI's (American Enterprise Institute) center for Health Policy Research. The volume bridges the debates of the 1970s and 1980s, thus laying the groundwork for future research by the Institute.
Proceedings of a conference sponsored by the Center for Health Policy Research of the American Enterprise Institute, held Sept. 25-26, 1980 in Washington, D.C.
Includes bibliographical references.
ne 5/06/2018
Loans
Keywords: Medical care; Medical policy; Medical economics; Health services